2003
DOI: 10.1080/0958519032000057565
|View full text |Cite
|
Sign up to set email alerts
|

High-involvement practices in human resource management: concept and factors that motivate their adoption

Abstract: Using data on 250 Spanish firms, we examine the incidence of high-involvement practices and investigate what variables are associated with the adoption of these practices. Particularly, we analyse the influence of size, age, competitive advantage, activity sector, the existence of a recent crisis, culture, leadership style and the competitiveness of the environment on the adoption of high-involvement work practices. With all this, we try to offer an exploratory view of nature of the contexts that condition the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 47 publications
1
36
1
10
Order By: Relevance
“…In addition, they pay greater attention to selecting and training expatriates (Welch & Welch, 1997). Finally, small firms that invest in HRM practices are more likely to implement integrated high performance work systems that are popular in developed countries (Ciavarella, 2004;Ordiz-Fuertes & Fernandez-Sanchez, 2003).…”
Section: Investing In Hrm In Entrepreneurial Firmsmentioning
confidence: 96%
“…In addition, they pay greater attention to selecting and training expatriates (Welch & Welch, 1997). Finally, small firms that invest in HRM practices are more likely to implement integrated high performance work systems that are popular in developed countries (Ciavarella, 2004;Ordiz-Fuertes & Fernandez-Sanchez, 2003).…”
Section: Investing In Hrm In Entrepreneurial Firmsmentioning
confidence: 96%
“…It should be noted that the proposition of strategy-HPWPs fit has received mixed support, with some studies demonstrating an interactive relationship between competitive strategy and HPWPs (e.g., Youndt, Snell, Dean, & Lepak, 1996) and others not demonstrating this interaction (e.g., Ordiz-Fuertes & Fernández-Sánchez, 2003). These findings indicate that the issue of fit between HR practices and the organizational context is more complex than has been addressed in literature.…”
Section: High-performance Work Practicesmentioning
confidence: 76%
“…Existing scholarly literature on HPWS has focused on various predictors such as management values (Bae and Lawler, 2000;, strategic HRM orientation (Lui et al, 2004;Galang, 1999), union density/militancy (Galang, 1999), external environment (Ordiz-Fuertes and Fernández-Sánchez, 2003), and trust (Tzafrir, 2005;Hansen and Alwell, 2012). This study based its theoretical core on Colquitt et al's (2007) study-which differentiated trustworthiness from trust and found that trustworthiness has an independent incremental effect on job performance and risk taking in organizations-and, extends this literature by testing trustworthiness as an antecedent for the adoption of HPWS.…”
Section: Theoretical Implicationsmentioning
confidence: 99%